In situ seismic testing of a reinforced autoclaved aerated concrete building: Seismische In‐situ‐Prüfung eines Gebäudes aus bewehrtem Porenbeton. Issue 5 (30th August 2018) - Binici, Baris; Gokmen, Furkan; Canbay, Erdem; Aldemir, Alper; Ogdu, Mustafa Kagan; Uzgan, Ugur; Eryurtlu, Zafer; Ozdemir, Gulay
Abstract: Autoclaved aerated concrete (AAC) reinforced panels are used to construct easily erected, energy efficient, low‐rise prefabricated buildings. This study aims to contribute to the understanding of the seismic response of reinforced‐AAC‐wall‐panel buildings. For this purpose, a full‐scale two‐story building constructed on a building site by using reinforced AAC panels was tested under two‐way cyclic displacement excursions up to near collapse. The test results showed that the test building had a lateral load capacity of 1.6 times its weight with a global displacement ductility of about 3.5. The first story of the building sustained significant damage due to the rocking of the building followed by panel crushing. The slab–wall connections did not sustain any damage during the test. Afterward, numerical models of AAC panels were calibrated by using component test results from the literature. Nonlinear static analysis was conducted on the test building by using the proposed modeling approach. A reasonably good agreement was observed between the test results and numerical model estimations both for the envelope and the cyclic response. Finally, incremental dynamic analyses were conducted on the test building in order to observe the response of the building under severe earthquake motions. The dynamic analyses results showed that AAC buildings are expected to behave in their pre‐yielding regions under design earthquakes. Furthermore, the reserved ductility and available over strength can enable AAC buildings survive the maximum considered earthquakes without collapse.